Relief of Cervicogenic Headaches after Single-Level and Multilevel Anterior Cervical Diskectomy: A 5-Year Post Hoc Analysis. (September 2016) - Liu, Jonathan J.; Cadena, Gilbert; Panchal, Ripul R.; Schrot, Rudolph J.; Kim, Kee D.
Study Design: Prospective study. Objective: Because single-level disk arthroplasty or arthrodesis in the lower subaxial spine improves headaches after surgery, we studied whether this effect may be better appreciated after two-level arthroplasty. Methods: We performed an independent post hoc analysis of two concurrent prospective randomized investigational device exemption trials for cervical spondylosis, one for single-level treatment and the other for two adjacent-level treatments. Results: For the one-level study, baseline mean headache scores significantly improved at 60 months for both the cervical disk arthroplasty (CDA) and anterior cervical diskectomy and fusion (ACDF) groups ( p  < 0.0001). However, mean improvement in headache scores was not statistically different between the investigational and control groups from 6 months through 60 months. For the two-level study, baseline mean headache scores significantly improved at 60 months for both the CDA and ACDF groups ( p  < 0.0001). The CDA group demonstrated greater improvement from baseline at all points; this difference was statistically significant at 6, 12, 24, 36, and 48 months but not at 18 and 60 months. Conclusion: Both CDA and ACDF at either one or two levels are associated with sustained headache relief from baseline. Patients undergoing two-level arthroplasty had significantly greater improvement in headache at all points except for at 18 and 60 months. This difference in improvement was not observed in patients undergoing single-level arthroplasty. The mechanism of greater headache relief after two-level arthroplasty remains unclear.